IS CROATIAN LEGISLATOR REDEFINING THE NOTION OF THE COURT: ANALYSIS FROM THE PERSPECTIVE OF THE CONVENTION LAW (EU and comparative law issues and challenges series (ECLIC), 2019)
The important doctrine in the case of the law of European Court of Human Rights (ECHR) is a “wide margin of appreciation” of the Member States when they take legislative or judicial actions. Moreover, national authorities are best acquainted with their regulations as well as other circumstances relevant to the adoption of specific laws. Therefore, they must assess which legal solution is the most appropriate. This is an advantage enjoyed by the national states, but they also have the responsibility for choosing the most appropriate legal solution. Therefore, legal disputes over the role of Judicial Advisors in simplified consumer bankruptcy procedure and enforcement procedure (according to the Draft of Enforcement Act) as persons conducting the procedure and persons obliged to render a decision, need to be analysed from the perspective of the standard “court established by law” according to Article 6 of the European Convention for the Protection of Human Rights and Fundamental Freedoms and Art. 29, 115 and 118 of the Constitution of the Republic of Croatia.